Training healthcare providers to respond to intimate partner violence against women - Kalra, Naira (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness of training programmes that seek to improve healthcare providers' identification of, and response to, IPV against women.